Critical Note The Authority Of TUN To The Cluster Of Government Administration Of Omnibus Law “Cipta Kerja” In Indonesia - Muhammad Ansor Lubis; Maswandi Maswandi (International Asia Of Law and Money Laundering (IAML), 2022)
In the concept of a state of law, everything must be done according to law, so that the government must submit to the law, not the law that must submit to the government, especially to the Mahakamh decision of the Constitution number 91/PUU-XVIII/2020 regarding the formal Uuck test that has broad consequences for the interests of the community, especially in testing the authority of TUN, such as the discretionary requirement that eliminates the “provisions in the legislation”, and changes in Article 53 of the Government Administration Law that releases the authority of TUN in testing the government's silence. The formulation of the problem in this paper is intended to provide a critical note and / or input for the improvement of the substance of UUCK to kewenagan Tun, especially in the cluster of Government Administration in Article 175 UUCK (changes to Law No. 30 year 2014 on Government Administration (ADPEM law)). Provisions that should be maintained or should be abolished. The research method used is normative jurisi research method. Normative research requires the approach of legislation (statute Approach) and conceptual approach. Data collection techniques used are through the study of documents and literature on secondary data in the form of primary, secondary and tertiary legal materials. The analysis used is descriptive. The conclusion in this paper is found that, first: Uuck's legal politics can be read as the spirit of the state in synchronizing, harmonizing, and eliminating sectoral egos; second: Uuck's provisions that must be maintained are Article 24 of the ADPEM law; third: the amendment to Article 53 of the ADPEM law on the “release “of the Administrative Court's authority in” testing " a government silence to be considered a positive fictitious decision is not necessary, because the Administrative Court's authority to test the government silence that is considered granted is important and vital